A documentação museológica para o diagnóstico de danos em cerâmicas arqueológicas - GUIMARÃES, Lívia Souza (2019)
Ceramics are important vestiges that can be found in sundry archaeological contexts, it is possible to understand the development processes and cultural choices through them and therefore their physical and informational values must be preserved. Identifying damages in fragments throughout the museological documentation enable to know the collection and adopt actions that allow the well-being to these materials and changes in laboratory practices. The diagnosis of damages was carried out through documentation of ceramics from the Ibama site (Melgaço-Pará), part of the Emílio Goeldi Museum's collection; they were selected and compared based on their morphological attributes and excavation points identified as top and bottom. The presence of certain alterations, such as cracks in the engobe layers, may be related to laboratory practices performed during curation processes. The few records of these practices, associated with a large amount of sorted materials, initiate a generalization of the collection without concern for its conservation condition.